2014
DOI: 10.1038/nn.3664
|View full text |Cite
|
Sign up to set email alerts
|

Designer receptors show role for ventral pallidum input to ventral tegmental area in cocaine seeking

Abstract: Ventral pallidum (VP) is centrally positioned within mesocorticolimbic reward circuits, and its dense projection to ventral tegmental area (VTA) regulates neuronal activity there. However, VP is a heterogeneous structure, and how this complexity affects its role within wider reward circuits is unclear. Here we demonstrate that projections to VTA from rostral (RVP), but not caudal VP (CVP) are robustly Fos-activated during cue-induced reinstatement of cocaine seeking—a rat model of relapse in addiction. Moreove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
402
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 327 publications
(428 citation statements)
references
References 51 publications
(83 reference statements)
24
402
2
Order By: Relevance
“…Within the addiction literature, these techniques are becoming the standard for NAc circuit manipulations (Stefanik et al, 2013b;Mahler et al, 2014b;Larson et al, 2015;Kerstetter et al, 2016). Another recent advance in genetic circuit deconstruction incorporates the tagging of neuronal ensembles during a specific behavior for later manipulations.…”
Section: Nucleus Accumbens: Connectivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Within the addiction literature, these techniques are becoming the standard for NAc circuit manipulations (Stefanik et al, 2013b;Mahler et al, 2014b;Larson et al, 2015;Kerstetter et al, 2016). Another recent advance in genetic circuit deconstruction incorporates the tagging of neuronal ensembles during a specific behavior for later manipulations.…”
Section: Nucleus Accumbens: Connectivitymentioning
confidence: 99%
“…Although modafinil is officially indicated only for the treatment of excessive daytime sleepiness, there is preclinical evidence to suggest that it may be used clinically for the treatment of substance use disorders. Importantly, for the purposes of this review, it appears that modafinil's efficacy against substance use disorders depends on glutamatergic signaling (Tahsili-Fahadan et al, 2010;Mahler et al, 2014b).…”
mentioning
confidence: 99%
“…Others have demonstrated that CNO alone has no effect on reinstatement behaviors or psychostimulant self-administration (Ferguson et al 2011;Mahler et al 2014;Scofield et al 2015;Augur et al 2016;Kerstetter et al 2016). However, Gomez et al implicate clozapine as the specific ligand to DREADDs and its back metabolism from CNO to engage DREADD-mediated changes in cell function (2017).…”
Section: Cno Administration Does Not Induce Reinstatement Behavior Inmentioning
confidence: 99%
“…Because pharmacokinetic studies report that CNO given i. p. at 1 mg/kg is eliminated from plasma within 2 h and reaches peak efficacy for 10 min to 10 h, we waited 30 min until testing and allowed 24 h for the drug effect to dissipate fully (Farrell and Roth, 2013;Ray et al, 2011). In the absence of DREADD expression, CNO administration at dose of ≥ 10 mg/kg has been reported to have no measurable effect across many monitored behavioral and physiological assays (Alexander et al, 2009;Mahler et al, 2014;Ray et al, 2011;Richards et al, 2014).…”
Section: Reversible Chemogenetic Inactivation Of the Dacc Neurons Dismentioning
confidence: 99%